Alat dan Media Pembelajaran Islam dalam Perspektif Al-Qur’an dan Hadist - Azizah Cahyani; Eka Syerlia Putri; Lathifah Khairani; Muhammad Irfan (Ta'lim: The Islamic Religious Educational Journal, 2026)
This study aims to describe the concept of teaching aids and learning media from the perspective of the Qur’an and Hadith and their relevance to the development of ethical and spiritual-based Islamic educational media. The research method used is library research with a tafsir tarbawi approach, which interprets Qur’anic verses and Hadith by emphasizing the educational values contained within them. The findings show that the Qur’an provides a conceptual foundation for the use of learning media through symbols, sensory perception, and parables, while the Hadith illustrates the Prophet Muhammad’s practical application of various media such as drawings, fingers, and tangible objects to clarify teachings. The discussion reveals that learning media in Islam not only serve as technical tools but also as means to build students’ morals and spirituality. In conclusion, this research presents a novelty in integrating Qur’anic and Prophetic values into the development of modern learning media grounded in tarbawi principles to achieve pedagogical effectiveness and spiritual harmony.